2011
DOI: 10.33899/csmj.2011.163617
|View full text |Cite
|
Sign up to set email alerts
|

An Approximate Solution to The Newell-Whitehead Equation by Adomian Decomposition Method

Abstract: In this paper, we solved the Newell-Whitehead equation approximately using Adomain Decomposition method and we have compared this solution with the exact solution; we found that the solution of this method is so close to the exact solution and this solution is slower to converge to the exact solution when we increase t however, this method is effective for this kind of problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…If we take a = 1, the fractional NWSE reduces to the classical NWSE (Macías-Díaz and Ruiz-Ramírez, 2011). The classical NWSE have been studied by Laplace Adomian decomposition method (Pue-on, 2013), Differential transform method (Aasaraai, 2011), Reduced Differential transform method (Saravanan and Magesh, 2013), Adomian decomposition method (Manaa, 2011), Homotopy perturbation method (HPM; Nourazar et al, 2011;Mahgoub, 2016), Cubic B-spline collocation algorithm (Zahra et al, 2014) and Variational iteration method . Some recent advances on HPM can be found in Skrzypacz et al, 2020;Anjum and He, 2020;In the past few decades, it has been observed that fractional analysis has tremendous applications in many branches of science.…”
Section: Introductionmentioning
confidence: 99%
“…If we take a = 1, the fractional NWSE reduces to the classical NWSE (Macías-Díaz and Ruiz-Ramírez, 2011). The classical NWSE have been studied by Laplace Adomian decomposition method (Pue-on, 2013), Differential transform method (Aasaraai, 2011), Reduced Differential transform method (Saravanan and Magesh, 2013), Adomian decomposition method (Manaa, 2011), Homotopy perturbation method (HPM; Nourazar et al, 2011;Mahgoub, 2016), Cubic B-spline collocation algorithm (Zahra et al, 2014) and Variational iteration method . Some recent advances on HPM can be found in Skrzypacz et al, 2020;Anjum and He, 2020;In the past few decades, it has been observed that fractional analysis has tremendous applications in many branches of science.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, this equation has been applied to various systems, e.g., nonlinear optics, biological systems, Rayleigh-Benard convection, and chemical reactions. In recent years, several techniques have been developed to solve the NWS equations, e.g., lattice Bolzmann scheme [14], Adomian decomposition method [15], finite difference scheme [16], differential transformation method [17], and reduced differential transformation [18].…”
Section: Introductionmentioning
confidence: 99%
“…, expresses the variations of ϑ(x, t) with spatial variable x at a specific time and the remaining terms on the right hand side, αϑ − βϑ γ , takes into account the effect of the source term. Recently, NWSE has been studied by Laplace Adomian decomposition method [31], Adomian decomposition method [24], differential transform method [1], cubic B-spline collection method [40], VIM [30] and HPM [21,28,29]. In current paper, we will study the VIM combined with HPM.…”
Section: Introductionmentioning
confidence: 99%